2020
DOI: 10.1108/jap-02-2020-0004
|View full text |Cite
|
Sign up to set email alerts
|

Safeguarding adults reviews and homelessness: making the connections

Abstract: Purpose This paper presents the results of a thematic analysis of safeguarding adults reviews (SARs) where homelessness was a factor to illuminate and improve safeguarding practice and the support of adults who are homeless in England. Design/methodology/approach SARs were identified from a variety of sources and a thematic analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…The main source for locating reviews was through searching Safeguarding Adults Board (SAB) websites for published SARs (November 2019). This approach has been used by other researchers (Manthorpe and Martineau, 2015; Martineau et al , 2019). Websites demonstrate marked variability in terms of accessibility and quality.…”
Section: Methodsmentioning
confidence: 99%
“…The main source for locating reviews was through searching Safeguarding Adults Board (SAB) websites for published SARs (November 2019). This approach has been used by other researchers (Manthorpe and Martineau, 2015; Martineau et al , 2019). Websites demonstrate marked variability in terms of accessibility and quality.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is arguable that discussions within SARs about social work practice may be orientated around the discourses of “what went wrong?” or “did we fail?”; alongside seeking examples of “good practice”. Several social work researchers have warned about the limitations of exploring social work from this position (Kettle, 2018; Martineau and Manthorpe, 2020; Preston-Shoot et al , 2022), suggesting that dominant discourses of harm and failure might be damaging to social work practice. If the only available narratives about social work are negative, will social work practice wisdom be fated to be negative from the outset?…”
Section: Background and Contextmentioning
confidence: 99%
“…The 1957 and 1966 papers both fastened on alcohol use as a prominent causal factor in the development of self-neglect (or social/senile breakdown as it was named). Recent analysis of Safeguarding Adults Reviews (SARs) where homelessness had been a factor identified an ambiguity in this area, where substance misuse and alcohol dependency were often prominent (Martineau and Manthorpe, 2020). One SAR, for example, described practitioners manifesting:…”
Section: Neglect Of Surroundings Neglect Of Selfmentioning
confidence: 99%
“…Recent work examining Safeguarding Adults Reviews of the care and support of people who were homeless (and Diogenes did present as street homeless) took a step back from simple refusal and suggested there were reasons on both sides of the encounter for poor engagement (Martineau and Manthorpe, 2020). Reviews evidenced a reluctance to engage on the part of individuals who were homelesssometimes this appeared to be the result of mental health problems or bound up with the itinerant nature of individual lives.…”
Section: Refusals and Interventionsmentioning
confidence: 99%
See 1 more Smart Citation